JUMLAH NEUTROFIL DI CAIRAN SULKUS GINGIVA PADA BINARAGAWAN ANGKAT BEBAN (Studi Komparasi pada Pengguna Steroid Anabolik dan Non Pengguna Steroid Anabolik) - Kurniawan Cahya Saputra; Sudibyo -; Hayyu Failasufa (Universitas Muhammadiyah Semarang, 2017)
Background : In medical terms anabolic steroid being use for deficiency treatment for testosterone, but along the way it have been misused as a doping for athletes which have bad side effect such as inflamation in periodontal tissue. The volume of sulcus gingival fluid will be increase if an infection occurs, one of the increasing components is neutrophils which are the initial defense to control infection in periodontal tissues. Purpose : To count the amount of sulcus gingival fluid on neutrophils anabolic steroid user and non anabolic steroid user. Thus research is using the analytic observational method with cross-sectional research design. The amount of the sampel has been given to 30 people devided into anabolic steroid user and non anabolic steroid user. Method : With paper point sulcus gingival fluid has been devided into group and they count the neutrophils. The count of data research been analized with independent T -test. Result : The differentiation of sulcus gingival fluid, theneutrophils amount has no significant differentiation founded between the controls group with the sampel group is p >0.05, this result caused by lots of factor that decrease the anabolic steroid effect.Conclution : Counterpart medicine, diet, and the PCT cause the unsignificant result on the meutrophils amount (p>0.05). Keywords: Anabolic Steroid, Sulcus Gingival Fluid, Athletes, Neutrophil.